Acceptability of a Prime Vendor System in Public Healthcare Facilities in Tanzania - August Kuwawenaruwa; Fabrizio Tediosi; Emmy Metta; Brigit Obrist; Karin Wiedenmayer; Vicky-Sidney Msamba; Kaspar Wyss (Kerman University of Medical Sciences, 2021)
BackgroundPharmaceutical supply chain management in low- and middle-income countries has received substantial attention to address the shortage of medicines at peripheral facilities. The focus has been on health system interventions, including the establishment of public-private partnerships (PPPs). In 2014, the United Republic of Tanzania began implementing the Jazia prime vendor system (Jazia PVS) with a contracted private wholesale supplier to complement the national medicines supply chain in public facilities. Few studies have investigated the acceptability of such a prime vendor system. This study analyses factors that contributed to the acceptability of Jazia PVS introduced in Tanzania. We used qualitative analytical methods to study experiences of Jazia PVS implementers in 4 districts in mid-2018. MethodsData were drawn from 14 focus group discussions (FGDs), 7 group discussions (GDs) and 30 in-depth interviews (IDIs) with a range of actors involved in Jazia PVS. The study analysed 7 acceptability dimensions as defined in the acceptability framework by Sekhon et al. Framework analysis was adopted to summarise the results using a deductive and an inductive approach. ResultsThe findings show that participants' acceptability of Jazia PVS was influenced by the increased availability of essential medicines at the facilities, higher order fulfilment rates, and timely delivery of the consignment. Furthermore, acceptability was also influenced by the good reputation of the prime vendor, close collaboration with district managers, and participants' understanding that the prime vendor was meant to complement the existing supply chain. Intervention coherence, experienced opportunity cost and intervention burden, affective attitude and self-efficacy were also important in explaining the acceptability of the Jazia PVS. ConclusionIn conclusion, the most critical factor contributing to the acceptability of the Jazia PVS was the perceived effectiveness of the system in achieving its intended purpose. Districts purchasing directly from the prime vendor have a policy based on the possibility to increase availability of essential medicines at peripheral facilities in a low income setting; however, it is crucial to select a reputable and competent vendor, as well as to abide by the contractual agreements.